2022
DOI: 10.3390/su14073842
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Uptake, Use Efficiency, and Productivity of Nigella sativa L. in Response to Fertilization and Plant Density

Abstract: Nigella sativa L. has been recognized as one of the most important medicinal plants in many parts of the world for centuries. The purpose of the current study was to evaluate the effects of fertilization and plant density on nitrogen uptake, utilization efficiency, and productivity of N. sativa under Mediterranean conditions. The three-year experiment was set up in a split-plot design with three replications. There were 2 plant densities; 200 and 300 plants m−2 with 4 fertilization levels: control, seaweed com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 78 publications
1
3
0
Order By: Relevance
“…Our results provide evidence that composted seaweed can in fact maintain but also moderately enhance soil N storage contributing to long‐term soil quality and fertility without compromising productivity. Roussis et al (2022) found that manure and seaweed compost as opposed to inorganic fertilization had the greatest influence on soil total nitrogen, which was attributed to the clear relationship with the increase in SOM as our results corroborated as well.…”
Section: Discussionsupporting
confidence: 88%
“…Our results provide evidence that composted seaweed can in fact maintain but also moderately enhance soil N storage contributing to long‐term soil quality and fertility without compromising productivity. Roussis et al (2022) found that manure and seaweed compost as opposed to inorganic fertilization had the greatest influence on soil total nitrogen, which was attributed to the clear relationship with the increase in SOM as our results corroborated as well.…”
Section: Discussionsupporting
confidence: 88%
“…Appropriate planting density and fertilisation rate are vital for securing a high crop yield and soil carbon (C) accumulation (Xu et al, 2017;Zhao et al, 2021;Roussis et al, 2022). Plant density (PD), an effective agronomic strategy in increasing maize (Zea mays L.) yield, ranged largely among regions and seemed too low.…”
Section: Introductionmentioning
confidence: 99%
“…Agronomic nitrogen utilization efficiency is defined as the direct increase in seed output per increased unit of N fertilizer [26]. Physiological nitrogen usage efficiency, on the other hand, is assessed as the nitrogen/carbon balance in the shoots at harvest, which is measured by examining the relationship between the biomass and N content of the shoots [27]. To the best of our knowledge, no evidence exists regarding the impact of nitrogen fertilization on the agro-morphological and yield attributes of S. alba in the Pothwar region of Pakistan.…”
Section: Introductionmentioning
confidence: 99%